2017
DOI: 10.24093/awej/vol8no3.9
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Teaching and Learning Principles in Classroom Practices

Abstract: Abstract:Vocabulary teaching and learning principles assist in providing effective teaching and learning methods, in accordance with the learners' proficiency level. However, studies that looked into the relevancy of those principles are rather limited. Thus, this study focuses on finding the common practices of vocabulary teaching and learning principles in the classroom. Interviews involving three experts were done to determine their vocabulary teaching and learning principles application in their teaching. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The study also showed that the participants linked the vocabulary to the past experiences and showed the objects (realia) to the students when they were available. This finding is in support of the study conducted by Ismail et al (2017), who reported that teachers used materials like real objects while teaching vocabulary to students. The study further showed that teachers related the target English words to the past experiences to depict the connection between new words and their meaning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study also showed that the participants linked the vocabulary to the past experiences and showed the objects (realia) to the students when they were available. This finding is in support of the study conducted by Ismail et al (2017), who reported that teachers used materials like real objects while teaching vocabulary to students. The study further showed that teachers related the target English words to the past experiences to depict the connection between new words and their meaning.…”
Section: Discussionsupporting
confidence: 90%
“…The researchers designed the questionnaire through reviewing the literature. The questionnaire items were adopted from other studies (i.e., Ismail et al, 2017;Lockhart, 2015;Tavakoli & Gerami, 2013;Zabidin, 2015). The questionnaire had three parts.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Appropriate load of vocabulary in ESL textbooks (Alqahtani, 2015) Balance of simple and complex words in the textbook (Dakhi & Fitria, 2019) There should be a balance of vocabulary presentation in the textbook (Ismail et al, 2017) Consist of adequate exercises for vocabulary learning (Nation, 2001) Contextualisation of vocabulary boosts the learners' confidence to comprehend the meaning independently (Alqahtani, 2015) The choice of vocabulary in textbooks should be suitable to be contextualised in order to assist students to understand the vocabulary (Rapaport, 2004) Vocabulary practices in the textbooks are the tools that teachers use to assist learners' vocabulary acquisition (Topical nature).…”
Section: The Principles Of Vocabulary Teaching In Esl Classroomsmentioning
confidence: 99%
“…Abilene Christian University conducted another research and found that the kids were highly motivated to complete their lessons on mobile devices than the learning they have done through traditional textbooks and workbooks (Rao, 2018) Other benefits of using mobile apps and its pedagogical impact is teaching and learning become more flexible and independent without neglecting the role of the teacher. Vocabulary acquisition depends not only on how learners learn, but also how they are taught (Ismail et al, 2017). Teachers are still needed for guidance purpose but students are given more room to participate in the learning process because students can use mobile apps outside of the classroom.…”
Section: Pedagogical Implicationmentioning
confidence: 99%
“…Language is comprised of vocabularies and it is the key for verbal communication. Language has given human being the ability to communicate with each other, forming a complex system of communication, and within each language vocabulary stands as the basis for the language (Ismail et al, 2017). Therefore, for us to be good language users and to communicate effectively, we have to acquire abundant vocabularies.…”
Section: Introductionmentioning
confidence: 99%